Experience of East Sumatra: Eradication of Disease Outbreaks, 1880”1940s - Darini, Ririn (Universitas Airlangga, 2023)
During the early phases of frontier expansion in East Sumatra, a notable surge in mortality rates, particularly within plantations, was observed due to widespread disease outbreaks. This study aims to illuminate the array of health issues linked to epidemics in East Sumatra, as well as the concerted efforts to mitigate them. Employing the historical method, the research encompasses four distinct stages: heuristics (source acquisition), source critique, interpretation, and historiography. Important sources include reports from plantation physicians, colonial health service documentation, and contemporaneous secondary references. Photographic evidence from the period is also incorporated to strengthen the analysis. The findings underscore East Sumatra's status as a plantation frontier, susceptible to a spectrum of outbreaks encompassing cholera, dysentery, malaria, and various other tropical diseases. These outbreaks elevated mortality rates. Subsequent enhancements to health services were implemented, including the establishment of proper hospitals, construction of quarantine facilities, tropical health research initiatives, vaccination campaigns, and advances in sanitation practices. Consequently, the mortality rate registered a significant decline.